2008
DOI: 10.1080/17439880802097634
|View full text |Cite
|
Sign up to set email alerts
|

Authentic learning and multimedia in history education

Abstract: A brief narrative description of the journal article, document, or resource. The momentum gathering behind authentic learning/critical skills raises fundamental issues concerning teaching and learning. This article discusses some of the more general arguments surrounding authentic learning with particular reference to an in-depth evaluation of its impact on schools in one part of Great Britain. It then moves on to describe how this approach to teaching and learning influenced the design of a multimedia CD-ROM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…An authentic activity learning environment provides a "real world" application or discipline (Robertson, 2014). Authentic learning usually focuses on the real world, complex problems, and their solutions, using role-playing exercises or role-playing, problem-based learning, case studies, and participation in virtual practice communities (Hillis, 2008;Slepkov, 2008). The learning environment is made inherently multidisciplinary.…”
Section: The Nature Of Authentic Learningmentioning
confidence: 99%
“…An authentic activity learning environment provides a "real world" application or discipline (Robertson, 2014). Authentic learning usually focuses on the real world, complex problems, and their solutions, using role-playing exercises or role-playing, problem-based learning, case studies, and participation in virtual practice communities (Hillis, 2008;Slepkov, 2008). The learning environment is made inherently multidisciplinary.…”
Section: The Nature Of Authentic Learningmentioning
confidence: 99%
“…Gilje and Erstad (2017) view authentic learning as one of the contemporary educational buzzwords. For example, authentic learning is discussed in connection with enterprise and entrepreneurship education (Gilje and Erstad 2017;Macht and Ball 2016), online and computer-assisted learning (Herrington, Oliver, and Reeves 2003;Herrington and Parker 2013), arts education (Russell-Bowie 2012), language education (Nikitina 2011), history education (Hillis 2008), social studies (Saye and Social Studies Inquiry Research Collaborative 2013) and technology education (Nicaise, Gibney, and Crane 2000;Snape and Fox-Turnbull 2013). Two decades ago, Schaffer and Resnick (1999) pointed out that the concept of authenticity is used with varying meaningsin varying contextsrather loosely and inconsistently.…”
Section: Authentic Learningmentioning
confidence: 99%
“…In this context, historians have concluded that computers can make important contributions to the teaching and learning history. Studies by past research showed that using multimedia computer technology in learning history significantly improve students' learning performance [15], [16].…”
Section: ) History and Technologymentioning
confidence: 99%